জ্ঞানতাপস আব্দুর রাজ্জাক স্মারকগ্রন্থ - রাজ্জাক, আব্দুর, ১৯১৪-১৯৯৯; আনিসুজ্জামান (ঢাকা : বেঙ্গল পাবলিকেশন্‌স, 2017)
Contributed articles on the life and works of Ābdura Rājjāka, 1914-1999, college teacher, educator and political activist from Bangladesh; commemoration volume.
Donated By Akbar Ali Khan
In Bengali; includes articles in English.
Keywords: Razzaq, Abdur, -- 1914-1999.; College teachers -- Bangladesh -- Biography; Educators -- Bangladesh -- Biography; Political activists -- Bangladesh -- Biography; Education